2021
DOI: 10.1007/s43440-020-00213-z
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside from ginseng: a promising treatment for inflammatory bowel disease

Abstract: Inflammatory bowel disease (IBD) is an autoimmune disease mediated by immune disorder and termed as one of the most refractory diseases by the Word Health Organization. Its morbidity has increased steadily over the past half century worldwide. Environmental, genetic, infectious, and immune factors are integral to the pathogenesis of IBD. Commonly known as the king of herbs, ginseng has been consumed in many countries for the past 2000 years. Its active ingredient ginsenosides, as the most prominent saponins of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 143 publications
0
20
0
Order By: Relevance
“…Ginsenosides have been extracted from the genus Ginseng’s roots, stems, leaves, and fruits ( Kang et al, 2021 ). Ginsenosides Rg1 can block the recognition of TLR, inhibit PI3K/Akt pathway transactivation and STAT protein activation, and regulate Follicular helper T cells (Tfh)/Treg cell homeostasis ( Jin et al, 2021 ).…”
Section: Natural Products and Ibdmentioning
confidence: 99%
“…Ginsenosides have been extracted from the genus Ginseng’s roots, stems, leaves, and fruits ( Kang et al, 2021 ). Ginsenosides Rg1 can block the recognition of TLR, inhibit PI3K/Akt pathway transactivation and STAT protein activation, and regulate Follicular helper T cells (Tfh)/Treg cell homeostasis ( Jin et al, 2021 ).…”
Section: Natural Products and Ibdmentioning
confidence: 99%
“…Several studies have reported that oral administration of Ginseng Radix et Rhizoma extracts shows promising anti-viral effects (e.g., lowering viral loads and improving the viability of infected cells) against human immunodeficiency virus-1, influenza virus, rotavirus, and respiratory syncytial virus [ 25 26 ] . Ginseng Radix et Rhizoma can ameliorate chronic inflammation induced by a variety of autoimmune diseases—such as rheumatic diseases and inflammatory bowel disease—presumably by inhibiting the release of inflammatory cytokines, such as IL-6 and TNFα [ 27 28 ] . In addition, a small-sized clinical study shows that administration of Ginseng Radix et Rhizoma Rubra extract reduced the production of inflammatory cytokines, such as TNFα and IFNγ, after chemotherapy [ 29 ] .…”
Section: Underlying Mechanisms Of Anti-fatigue Effects Of G...mentioning
confidence: 99%
“…Besides CK, other gut microbial metabolites of ginsenosides have been found to possess anti-inflammatory and anti-IBD effects via various mechanisms [90,117].…”
Section: Ginsenosidesmentioning
confidence: 99%